3(-4x)=-2(6x-9)

Simple and best practice solution for 3(-4x)=-2(6x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-4x)=-2(6x-9) equation:


Simplifying
3(-4x) = -2(6x + -9)

Remove parenthesis around (-4x)
3 * -4x = -2(6x + -9)

Multiply 3 * -4
-12x = -2(6x + -9)

Reorder the terms:
-12x = -2(-9 + 6x)
-12x = (-9 * -2 + 6x * -2)
-12x = (18 + -12x)

Add '12x' to each side of the equation.
-12x + 12x = 18 + -12x + 12x

Combine like terms: -12x + 12x = 0
0 = 18 + -12x + 12x

Combine like terms: -12x + 12x = 0
0 = 18 + 0
0 = 18

Solving
0 = 18

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3(y-4)-4=2y+6.9 | | (-.8)(1/5)=x | | 8y=11y+3 | | w/11=3 | | 6+2(8f-2)=4(1+f) | | 6.2x-5+x-1.5=0 | | p=180*(33.333/100) | | (-4)-(-.8)=x | | (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 | | 3/x=5/2x | | 8z+33=3(3z+11)-z | | 89=x+13(7) | | 12x^2-(121/12)=0 | | -5(x-3)=10 | | -3(2x+2)=6x-8 | | 69=3(4x-1) | | 4x-1+2x-1=5y | | -5x-19=10 | | 15x+25y=120 | | 1y=3x-3 | | 915=10a-7 | | 5(3)-7=2(3+1) | | 94+27t=715 | | 5x-4(x+2)=29 | | =-4h+5j-4j+7h | | 5(x-3)=14 | | (2x)/7=2x^2 | | 5(2x-4)+7=12+3(2x+1) | | 816=24(v+12) | | 3)x-y)/5(2x/3y) |

Equations solver categories